Predictivity and Manifestation Factors in Aging Effects on the Orienting of Spatial Attention. (25th May 2019) - Zivony, Alon; Erel, Hadas; Levy, Daniel A
Abstract: Objective: Prior attention research has asserted that endogenous orienting of spatial attention by willful focusing may be differently influenced by aging than exogenous orienting, the capture of attention by external cues. However, most such studies confound factors of manifestation (locational vs symbolic cues) and the predictivity of cues. We therefore investigated whether age effects on orienting are mediated by those factors. Method: We measured accuracy and response times of groups of younger and older adults in a discrimination task with flanker distracters, under three spatial cueing conditions: nonpredictive locational cues, predictive symbolic cues, and a hybrid predictive locational condition. Results: Age differences were found to be related to the factor of cue predictivity, but not to the factor of spatial manifestation. These differences were not modulated by flanker congruency. Discussion: The results indicate that the orienting of spatial attention in healthy aging may be adversely affected by less effective perception or utilization of the predictive value of cues, but not by the requirement to voluntarily execute a shift of attention.